2019
DOI: 10.1093/beheco/arz070
|View full text |Cite
|
Sign up to set email alerts
|

The costs of competition: injury patterns in 2 Asian colobine monkeys

Abstract: Aggression rarely escalates to physical conflict because doing so puts individuals at risk of injury. Escalation only pays off when the potential benefits outweigh the potential costs, that is, when resources critical to fitness are at stake. Here, we investigated the occurrence of injury in 2 Asian colobine species: Nepal gray langurs (Semnopithecus schistaceus) and Phayre’s leaf monkeys (Trachypithecus phayrei crepusculus). In both species, younger individuals are higher-ranking and might have greater incent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 109 publications
0
6
1
Order By: Relevance
“…In other nonhuman primates integrating individuals of the dispersing sex have been found to be more likely to be injured (Feder et al, 2019;MacCormick et al, 2012). In our study, we also observed injuries to some of the integrating males, although there were too few instances to include these observations formally in our models.…”
Section: Discussioncontrasting
confidence: 37%
“…In other nonhuman primates integrating individuals of the dispersing sex have been found to be more likely to be injured (Feder et al, 2019;MacCormick et al, 2012). In our study, we also observed injuries to some of the integrating males, although there were too few instances to include these observations formally in our models.…”
Section: Discussioncontrasting
confidence: 37%
“…These outcomes may be linked to differences in habitat and dietary specialization. Limited data suggest that gray langurs may spend more time on terrestrial substrates (Feder, Lu, Koenig, & Borries, 2019; Hladik, 1977), and consume a more diverse diet compared to purple‐faced langurs (Hladik, 1977), which are more strictly arboreal and folivorous. Accordingly, gray langurs have a less specialized gut (reduced stomach and expanded large intestine ) compared to purple‐faced langurs (Chivers & Hladik, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Concerning sex differences in contest damage, there are data for primate species showing that males receive more injuries than females [43]. Most likely, similar results could be found in many social species.…”
Section: Discussionmentioning
confidence: 62%